KAJIAN ETNOZOOLOGI UNTUK OBAT-OBATAN MASYARAKAT DAYAK BELANGIN DI DESA MUâ€™UN KECAMATAN NGABANG KABUPATEN LANDAK - Heningsih, Maria; Anwari, Sofwan; Yani, Ahmad (JURNAL HUTAN LESTARI, 2018)
Local people of Â Kalimantan still use natural products such as animals, plants or fruits in the forest for their daily needs, whether for consumption, customs, needs for medication, and other needs. One of them is the Dayak Belangin Communities located in the village of Mu'un, Ngabang District, Landak Regency. The purpose of this study was to obtain data on what kinds of animals are used for medicines and obtain data of animal utilization for medicines by the Dayak Belangin in Mu'un Village, Ngabang Sub-district, Landak Regency. This research used survey and interview method as well as direct observation in the field and tools used for data collection in the form of kouesioner. Based on the results of research conducted on 20 respondents it is known that the number of animal species still used for medecine by the Dayak Belangin Mu'un Village as many as 10 species. Parts of the body used for medicine in the form of whole body, bile, intestine, geliga, fat, bones and honey. Processing as a medicine by burning, boiling or soaking the parts of the body used and how to use it by drinking, eaten and polished.Keyword: Dayak Belangin, etnozoological, medecine.